Revisión a profundidad de la tasa de concepción en programas de inseminación artificial a término fijo en el ganado: El caso colombiano - Tuberquia-López, Brahian C. (2024)
The aim of this study was to collect and evaluate the scientific evidence on the results of the conception rate in female bovine animals in Colombia in fixed-term artificial insemination (FTAI) programmes during the last 10 years. The review was carried out according to PRISMA-ScR guidelines. Only original articles published in indexed journals and undergraduate and graduate thesis works reporting studies on Colombian cattle were considered. Twenty studies were selected (6 primary articles and 14 undergraduate and graduate works), covering 1464 cows and heifers. Dual-purpose cows reached the highest percentages (53.8%), while Bos indicus heifers recorded the lowest (37%). Of the total studies on heifers (30%), 51% focused on dual-purpose cows, 43% on breeding cows and 6% on dairy cows. The most used ovulation synchronization protocol included the use of progesterone, oestrogen, prostaglandins and equine chorionic gonadotropin. It is concluded that the choice of an insemination protocol and its effectiveness will be influenced by a wide variety of factors, so it is not prudent to define whether there is a synchronization protocol superior to the others. However, the use of equine chorionic gonadotropin showed to increase the conception rate in Colombian cattle.